Consolidation of soft clay around vertical drain - Nie, Xiao Yan. (2008)
Vertical drains combined with precompression by surcharge loading is an effective soil-improvement method and has gained wide interest and recognition. The use of vertical drains in soft clayey soils can (a) shorten the drainage paths and accelerate the primary consolidation settlements; (b) decrease time required for preloading before foundation construction; (c) increase shear strength of the soil and improve the stability of structure. In this study a numerical method has been developed for simulating the variation of soil permeability during the consolidation process and predicting the performance of vertical drains by taking this variation into account. In addition to the traditional Carey's law, non-Darcian flow proposed by Hansbo, was also incorporated in this study. The inclusion of non-Darcian flow adds greater versatility to the program and enables an assessment of the effect of non-Darcian flow on the consolidation process if the flow obeys such a nonlinear rule.